Frequency and syndrome specificity of antibodies to aquaporin-4 in neurological patients with rheumatic disorders - Jarius, Sven; Jacobi, Christian; de Seze, Jerome; Zephir, Helene; Paul, Friedemann; Franciotta, Diego; Rommer, Paulus; Mader, Simone; Kleiter, Ingo; Reindl, Markus; Akman-Demir, Gulsen; Seifert-Held, Thomas; et al. (Multiple sclerosis journal, 2011)
Background: A new autoantibody (termed NMO-IgG, or AQP4-Ab) has recently been described in patients with neuromyelitis optica (NMO) and its formes frustes, longitudinally extensive transverse myelitis (LETM) and recurrent optic neuritis (rON). However, AQP4-Ab has been found also in patients with co-existing rheumatic diseases such as systemic lupus erythematosus (SLE) or Sjögren’s syndrome (SS), conditions which are characterized by broad, polyspecific B cell activation., Objectives: In this study, we aimed at evaluating the syndrome specificity and frequency of AQP4-Ab in patients with rheumatic diseases and neurological symptoms., Methods: For this purpose, serum samples from 109 neurological patients with established connective tissue disorders (CTD) (n = 54), possible CTD (n = 42), or vasculitis (n = 13) were analysed for the presence of AQP4-Ab by a cell-based assay employing recombinant human AQP4., Results: AQP4-Ab was detectable in 31/40 (78%) patients with CTD and NMO spectrum disorders (median titre, 1:1000) but in none of the samples obtained from patients with CTD or vasculitis and neurological disorders other than NMO, LETM, or rON (n = 69)., Conclusion: The high syndrome specificity of the antibody for neuromyelitis optica spectrum disorders (NMOSDs) in patients with CTD supports the concept of AQP4-Ab being involved in the pathogenesis of these neurological conditions, and argues against AQP4-Ab simply being part of the polyclonal B cell activation generally associated with rheumatic diseases. Moreover, the finding that AQP4-Ab is present in patients with CTD and co-existing NMOSD with approximately the same frequency as in patients without CTD strengthens the case of CTD and AQP4-Ab positive NMOSD representing two co-existing yet distinct entities in the majority of patients.
Gesehen am 04.07.2022